Brand Image, Customer Experience, and Customer Value on Customer Satisfaction at Janji Jiwa Coffee in Pekanbaru City - Amin, Amirudin M.; Zhuo, Seliana (Luxury: Landscape of Business Administration, 2026)
This study aims to analyze the influence of brand image, customer experience, and customer value on customer satisfaction of Kopi Janji Jiwa in Pekanbaru City. This study was conducted in Pekanbaru City, with a population of consumers at Kopi Janji Jiwa whose number is unknown. Using the Roscoe method, a sample of 150 people was determined. The sampling technique in this study used accidental sampling. The data analysis method used multiple linear regression. The results of this study indicate that brand image has a significant influence on customer satisfaction of Kopi Janji Jiwa in Pekanbaru City. Furthermore, customer experience has a significant influence on customer satisfaction of Kopi Janji Jiwa in Pekanbaru City and customer value has a significant influence on customer satisfaction of Kopi Janji Jiwa in Pekanbaru City. The adjusted R Square value of 0.550 means that the influence of brand image, customer experience, and customer value on customer satisfaction is 55%, while the remaining 45% is influenced by other variables not used in this study.